Dynamics of Use of Water Resources of Khorezm Region - Namozov Jurabek Abduazizovich; Tohirova Muhayyo Hamid qizi (Genius Journals, 2023)
In the article, water resources, which are important for agriculture, especially in the current conditions, are becoming scarce, and regional problems in their use are considered on the example of Khorezm region. Gradual changes of water resources used for agriculture in the region are described based on the data of the left bank Amudarya Irrigation Systems Basin Administration of the Ministry of Water Management of the Republic of Uzbekistan. Changes in the amount of water used for the irrigated lands of the region in 2010-2021, periodic differences in water supply and its territorial characteristics were scientifically analyzed. In the conclusion, some suggestions and recommendations are given for solving problems related to water resources in the region
Keywords: water resources; Khorezm region; irrigated lands; salt washing